Financial corruption and investment opportunities in the Iraqi economy - عيسى, رجاء عبد الله (Journal of Economics and Administrative Sciences, 2012)
Corruption is one of the barriers to economic growth and investment opportunities, and after the most serious security and stability, that corruption plagued the Iraqi economy is striking and has roots since the eighties of the last century to the present day.The study aimed to identify practical impact of corruption on investment in the Iraqi economy and revealed the possibilities and obstacles to investment in Iraq and clarify the investment opportunities at the level of Iraq and the impact of corruption on investments. The focus will be on the statement of the extent of corruption and investment in Iraq and the adoption of the style of economic measurement using cross-sectional data for each of the level of corruption and investment allocations in the Iraqi ministries for the year 2007. The results of the study and a negative impact of corruption on investment and this is consistent with the logic of economic theory and the standard